The beginning of paramagnetic resonance - Kochelaev, B. I (World scientific, 1995)
Includes bibliographical references and index.; The discovery of Electron Paramagnetic Resonance is one of the outstanding events in Physics of the 20th Century. This phenomenon, connected with EPR, penetrates deep into the world of substances and has wide application in various spheres of the human activities. It was discovered by E K Zavoisky during the Second World War. This book covers what proceeded his success, his approach and how Kazan was transformed into a significant center of research in the field of radiospectroscopy.